Effect of the administration of polyethylene glycol (PEG) on the milk fatty acid composition of sheep grazing Sulla (Hedysarum coronarium) - Cabiddu A.; Decandia M.; Addis M.; Spada S.; Fiori M.; Piredda G.; Sitzia M.; Fois N.; Molle G. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
Tannins are naturally occurring polyphenols found in many forage plants that reduce their nutritional value through an inhibitory effect on ruminal and intestinal functions. Daily supplementation with polyethylene glycol (PEG) has been proven to efficiently neutralise the negative effect of tannins. A grazing experiment was undertaken to evaluate the effect of PEG supplementation on animal performance and milk fatty acid composition of Sarda sheep grazing sulla (Hedysarum coronarium). Twenty-four late-lactating sheep (12 per group), were paired and split into two groups: group CON daily dosed by a quenching gun with 200 ml of water, and group PEG, dosed with 200 ml of a 50/50 water solution of PEG. The sheep rotationally grazed two 0.8 ha plots of sulla. Milk yield tended (P<0.13) to be increased by PEG. Milk fat and protein contents were not affected by the treatment. The CLA (C18:2 c-9, t-11) and vaccenic acid (C18:1 t-11) contents in milk fat were higher on average by 40% for PEG than CON group. This can be explained by a higher biohydrogenation activity of ruminal bacteria in the PEG group, due to the partial inactivation of tannins. Actually both linoleic (C18:2 c-9 c-12) and linolenic (C18:3 c-9 c-12 c-15) fatty acid were lower (P<0.05) in milk from PEG than CON group (-12% and -30% for linoleic and linolenic acids, respectively).
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)